Pengaruh Penggunaan Media Audio Visual melalui Film Dokumenter terhadap Kemampuan Pemahaman Konsep Matematika - Maria Magdalena Sero (Universitas Indraprasta PGRI, 2016)
This experimental research aims to determine the effect of using audio-visual media through a documentary film on the ability of understanding mathematical concepts. The benefits of the audio-visual media through documentaries to facilitate learners in understanding the subject matter to be studied. The design used was experimental design true experimental design with posttest only control the shape design. This research was conducted among students of class VII in SMP Maria Media trix which is located at Jln. Pinus II No. 1 Pondok Rejeki, Kuta Baru, Pasar Kemis, Tangerang in the second semester of academic year 2015-2016. Samples were taken two classes at random from the seven existing parallel class, then placed as two groups of samples, the experimental group (class VII.2) and the control group (class VII.3). After two sample groups were given different treatment, each sample group were given a posttest with the instrument consists of 10 items essay form. The instrument has been tested and validated beforehand. Analysis of the data using the